Spoken Model Texts and Students’ Produced Spoken Texts in a State Junior High School in Surabaya (RETAIN, 2016)
Spoken Model Texts and Students’ Produced Spoken Texts in a State Junior High School in Surabaya Cicilia Reny Wijaya English Education, Faculty of Language and Arts, State University of Surabaya Ciciliawijaya@mhs.unesa.ac.id Ahmad Munir English Education, Faculty of Language and Arts, State University of Surabaya ahmadmunir@unesa.ac.id Abstrak Penelitian ini berkaitan dengan teks model lisan dan teks produksi lisan siswa dalam pembelajaran bahasa Inggris. Penelitian ini menjawab apakah teks lisan produksi siswa mencerminkan model teks lisan yang diberikan guru. Studi kasus digunakan dalam penelitian ini. Seorang guru instruktur nasional bahasa Inggris di sebuah SMP Negeri di Surabaya terpilih sebagai subyek dari penelitian ini. Data dikumpulkan melalui dokumentasi RPP dan observasi proses pembelajaran. Kemudian, data dianalisis secara kualitatif. Hasil dari penelitian ini menunjukkan bahwa hanya ada sedikit kemiripan dari teks lisan produksi siswa dengan teks model lisan. Kata Kunci: teks, teks lisan, teks model, teks produksi Abstract This study deals with spoken model texts and produced students’ spoken texts in the English learning process. The objective of this study is to find out whether the students’ produced spoken texts resemble the spoken model texts. A case study was applied in this research. A national instructor English teacher of 2013 curriculum in a state junior high school in Surabaya was chosen as the subject of this study. The data were collected by documentation of the lesson plan and observation of the learning process. Then, the data were analyzed qualitatively. This study found out that there was a little resemblance of the students’ produced spoken texts to the spoken model texts. Keywords: text, spoken text, model text, produced text.